Democracy, political fragmentation and budget deficits : evidence from Asian countries - Cheng, Adrian Sai Pong (2015)
One of the most debated issues in economics in recent years is the extent of budget deficits and public debt. Given the failure of standard economic theories in explaining the cross-national variations of fiscal outcomes, scholars in political economy have turned to political factors to account this phenomenon. However, much of extant literature is on OECD countries and their findings have limited applicability outside the OECD context, especially in regions where there is wide variation in the level of democracy. Moreover, it is only in the more recent years that scholars begin to explore the interaction between political factors in influencing fiscal policy outcomes. Using panel data for 19 countries in Asia over the period 1980-2012, we empirically investigate the interactive effect between democracy and political fragmentation on budget balance. We find strong evidence that the net effect of democracy is dependent on the extent of political fragmentation.